Network Centrality and Managerial Market-Timing Ability - Evgeniou, Theodoros; Peress, Joel; Vermaelen, Theo; Yue, Ling (Journal of Financial and Quantitative Analysis, 2022)
Abstract We document that long-run excess returns following announcements of share buyback authorizations and insider purchases are a U-shaped function of firm centrality in the input–output trade-flow network. These results conform to a model of investors endowed with a large but finite capacity for analyzing firms. Additional links weaken insiders’ informational advantage in peripheral firms (simple firms whose cash flows depend on few economic links), provided investors’ capacity is large enough, but eventually amplify that advantage in central firms (firms with many links) as a result of investors’ limited capacity. These findings shed light on the sources of managerial market-timing ability.